Technique of adaptive e-learning courses development - Артамонов, Є. Б.; Кашкевич, І.-Ф. Ф. (Problems of Informatization and Control, 2016)
One of the tasks of the higher school informatization is to improve the quality ofspecialists/experts/professionals training through the introduction of information-educationalenvironment with remote access to content. But when working remotely with educational resources itis complicate to establish the teacher-student communication and impossible to make flexibleadaptation of the course to the user requirements. The article discusses the technique of adaptive elearningcourses development through the analysis of user requirements and their basic level ofknowledge